Non-digestible carbohydrates as an alternative to improve the technological and nutritional quality of meat products and potential application in fish burgers (Research, Society and Development, 2020)
Fish meat has a rich nutritional composition, but the per capita consumption of this food is low. A strategy to increase the intake of fish is found in the development of fish meat products, such as hamburgers. However, fish meat after comminuted, structured, frozen and thawed has a high syneresis. The use of non-digestible carbohydrates presents an alternative to increasing the dietary fiber content and the water retention capacity in meat products such as fish burgers. Therefore, the objective of the present study was to carry out a systematic review about the functional properties, application and performance of dietary fibers in meat products and fish hamburgers available on important scientific bases, preferably in the last five years. Through the studies, it was noted that the dietary fibers available for food industry and the characteristics exhibited by each one, as well as the application in meat products directly influence the sensory, physical-chemical and microbiological properties. The balance between soluble and insoluble fibers and the quantity added is essential to obtain products with the desired characteristics and quality. Thus, the formulation of hamburgers with the addition of dietary fiber can be advantageous, increasing the intake of foods with ingredients beneficial to health.